The italian zoological gardens and their role in mammal systematic studies, conservation biology and museum collections - Spartaco Gippoliti; Andrew Kitchener (Hystrix, the Italian Journal of Mammalogy, 2008)
Abstract
The opportunities offered to scientific research by living mammal collections are generally overlooked in Italy. This paper presents a short historical overview of the scientific investigations done on captive mammals from Italian zoos, especially those concerning taxonomic research. A glimpse of the opportunities offered by zoo specimens for scientific research is presented utilising examples from the National Museums Scotland.
The importance of increasing care in the identification of individual animals by studbook and ISIS numbers is also highlighted. We argue that a stronger collaboration between zoos, museums and universities is needed to maximise the scientific and conservation value of Italian mammal collections.

Riassunto
I giardini zoologici italiani e il loro ruolo negli studi sistematici sui mammiferi, biologia della conservazione e collezioni museali.
Generalmente, in Italia, le opportunità scientifiche offerte dai reperti provenienti da giardini zoologici sono sottovalutate. Il presente lavoro offre una sintesi storica delle ricerche, soprattutto di carattere tassonomico e sistematico, realizzate su materiale di zoo italiani. Vengono presentati poi esempi delle ricerche compiute presso i National Museums della Scozia
utilizzando materiale proveniente da zoo di tutta Europa, e le loro ricadute nel campo della sistematica, biologia della conservazione e benessere animale. Viene evidenziata la necessità di incrementare le informazioni concernenti ogni individuo in cattività, anche utilizzando i sistemi identificativi quali studbook e ISIS, per massimizzarne il valore
scientifico. Si conclude chiedendo una maggiore collaborazione tra zoo e musei italiani, a tutto vantaggio della comunità scientifica nazionale.